Educational Attainment and the Gender Gap in Childcare in Canada: A Decomposition Analysis. (November 2018) - Buchanan, Tom; McFarlane, Adian; Das, Anupam
Using the 2010 General Social Survey in Time Use (Canadian Time Diary data set, N = 1782), we explore the relationship between the education level of couples and the time they spend on childcare. We find that fathers and mothers with higher levels of educational attainment spend more time parenting children. However, the education childcare gradient is stronger for mothers than fathers. Consequently, the gender gap in childcare is much greater for couples with more educational attainment. The Blinder–Oaxaca decomposition results of these gender gaps by education level suggest very little can be attributed to how mothers and fathers at different levels of education differ on demographic and workplace characteristics. We argue that the differences in parenting time accompanying socio-economic status are more likely attributed to differences in parenting values. JEL Classifications: I24, J13, J16, C10